Application of Mobile Applications in Teaching English Phonology in Elementary Schools - Lubis, Yani; Adelia, Devi; Husni, Putri Nabila; Hawa, Pratiwi; Rizkiara, Ine (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2024)
Application of Mobile Applications in Teaching English Phonology for elementary school students to learn English independently, interestingly, and can be used whenever and wherever they are. One method that can increase interest and vocabulary in English for elementary school students is by creating interesting and unique learning media. Well-designed learning media can foster interest in learning and improve the quality of school education. The aim of this research is to determine the benefits of implementing mobile applications in teaching English phonology in elementary schools. The method in this research uses a qualitative method. The results of this research, the application of mobile applications in teaching English phonology in elementary schools, can help elementary school students in listening training , becoming interactive games in learning English, practicing vocabulary and speaking (speeking).